Childhood executive control and adolescent substance use initiation: the mediating roles of physical and relational aggression and prosocial behavior. Issue 2 (17th February 2023) - Patwardhan, Irina; Guo, Ying; Hamburger, Emily R.; Sarwar, Saira; Fleming, Charles B.; James, Tiffany D.; Nelson, Jennifer Mize; Espy, Kimberly Andrews; Nelson, Timothy D.; Mason, W. Alex
ABSTRACT: Although predictive associations between childhood executive control (EC) and adolescent substance use have been established in prior research, the developmental pathways involved in these long-term links have not been well understood. The goal of the current study was to investigate the degree to which aggressive behaviors, including both physical and relational aggression, and prosocial behaviors in elementary school operate as developmental pathways between preschool EC and adolescent substance use, while accounting for participants' age, sex, family history of substance use, and family socioeconomic status. Participants were 329 youth (49% male; 63.6% European American) who were recruited to participate in a study between 2006 and 2012 while youth were in preschool and elementary school and followed into adolescence. The sample was recruited from a small Midwestern city in the United States. EC was assessed with performance-based tasks when children were 5 years 3 months. Youth behaviors with peers were reported by teachers when participants were in elementary school. Self-reports of the substance use initiation (e-cigarettes, cigarettes, alcohol, and marijuana) were obtained in adolescence via phone surveys. Mediation analyses revealed a statistically significant indirect effect from preschool EC to adolescent substance use through youth's engagement in relational aggression in elementary school ( b = > −0.22 [−0.51; −0.08]; β = > −0.18). Our results suggest that developmental pathways to adolescent substance use may begin in preschool, setting the stage for susceptibility to engagement in relational aggression, which increases, in turn, youth's likelihood for substance use initiation in adolescence.